Sophisticated rGO synthesis and pre-lithiation unlocking full-cell lithium-ion battery high-rate performances. (10th December 2020) - Denis Louis Campéon, Benoît; Yoshikawa, Yumi; Teranishi, Takashi; Nishina, Yuta
Highlights: Combine chemical and thermal reduction methods were employed for the synthesis or reduce graphene oxide. Best graphene for LIBs was prepared via combined chemical and thermal reductions. Best reduced graphene oxide shows 947 mAh g −1 at 372 mA g −1 . Correlation of behavior was observed between SSA and capacity, conductivity and capability, and oxygen level and cyclability. Assembled high-rate full-cell LIBs displayed high energy and power density, 293 Wh kg −1 at 8658 W kg −1 . Abstract: For the application to portable devices and storage of renewable energies, high-performance lithium-ion batteries are in great demand. To this end, the development of high-performance electrode materials has been actively investigated. However, even if new materials exhibit high performance in a simple evaluation, namely half-cell tests, it is often impossible to obtain satisfactory performance with an actual battery (full cell). In this study, the structure of graphene analogs is modified in various ways to change crystallinity, disorder, oxygen content, electrical conductivity, and specific surface area. These graphene analogs are evaluated as negative electrodes for lithium-ion batteries, and we found reduced graphene oxide prepared by combination of chemical reduction and thermal treatment was the optimum. In addition, a full cell is fabricated by combining it with LiCoO2 modified with BaTiO3, which is applicable to high-speed charge–discharge cathode material developed in our previous research. In general, pre-lithiation is performed for the anode when assembling full cells. In this study, we optimized a "direct pre-lithiation" method in which the electrode and lithium foil were in direct contact before assembling a full cell, and created a lithium-ion battery with an output of 293 Wh kg −1 at 8, 658 W kg −1 .